2019
DOI: 10.1093/jisesa/iez001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Adults ofHermetia illucens(Diptera: Stratiomyidae) on Longevity, Oviposition, and Egg Hatchability: Insights Into Optimizing Egg Production

Abstract: Larvae of the black soldier fly, Hermetia illucens (L.), have been widely studied for their capacity of generating value-added products through waste bioconversion. Several efforts have been made towards optimization of rearing methods of the larval stages. Despite this, less information regarding the feeding behavior of adults and its effects on life parameters is available. We studied the impacts of subjecting adults to four diets: no diet (control); drinking water (water); a mix of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 39 publications
6
59
0
Order By: Relevance
“…Although abundant studies were performed on the optimization of larvae rearing [3,[14][15][16][17], additional information on the adult breeding strategies must be deepened. Expanded knowledge on the individual reproductive potential of females, adult density and nutrition requirements [18,19], may increase egg production and achieve a successful industrial process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although abundant studies were performed on the optimization of larvae rearing [3,[14][15][16][17], additional information on the adult breeding strategies must be deepened. Expanded knowledge on the individual reproductive potential of females, adult density and nutrition requirements [18,19], may increase egg production and achieve a successful industrial process.…”
Section: Introductionmentioning
confidence: 99%
“…The fecundity of females may be influenced by the nutritional content available during larval stages [3,28] or by the type of nutrition administrated during adult stage [17,18]. Moreover, a diet rich in proteins could increase the oviposition performances of BSF females [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may also invest less in nutrient acquisition during larval development because they have fewer digestive enzymes compared to BSFs [46], or because they must feed as adults to mature reproductively [47]. Black soldier flies, on the other hand, do not necessarily have to feed as adults [28] although they can [48,49]; there is an adaptive value for BSFs to invest in more digestive enzymes to feed more efficiently as larvae and acquire all of the nutrients needed to sustain adult livelihood [50].…”
Section: Discussionmentioning
confidence: 99%
“…In the future, therefore, research should investigate the effect of BSF-based feed on sensory attributes of animal products in Kenya. In BSF colonies, studies have shown that feeding adult BSF increases the oviposition period (Bertinetti et al, 2019;Chia et al, 2018b). However, little is known about the number of egg batches an adult BSF can lay in its life time.…”
Section: Future Perspectivesmentioning
confidence: 99%